Analytical and graphical methods for the solution of one problem of transport logistics - K. Zhetpisov; N.G. Karbenova (Қарағанды университетінің хабаршысы. Математика сериясы, 2017)
This article shows the way to solve a specific problem of transport logistics using the potential method. The first support plan is constructed by the method of the north - western corner. The article also shows a graphical method for solving the problem. The article shows the optimal method for solving the problem of transport logistics using the example of the real economy of the Kostanay region (Arkalyk).